Protean Career Development And Social Compensation On Employee Performance Balai Konservasi Sumber Daya Alam (BKSDA) Jawa Tengah - Bayu aldo kistara; Dias wahyu anggreani; Silvianna fatmawati; Dewi Agustina; Ratih Pratiwi; Samsoo Sa-U (CV Putra Publisher, 2022)
This study aims to determine the partial and simultaneous effect of protean career development and social compensation on performance of Balai Konservasi Sumber Daya Alam (BKSDA) Jawa Tengah employees. This study uses an associative approach to determine the relationship between the independent variables and the dependent variable. The population in this study were 160 employees. The sample that will be used in this study uses the Slovin formula with a significance level of 10% and a sample of 62 employees is obtained. Data collection using questionnaires and data analysis using multiple linear regression analysis. The results of this study indicate that the protean career development variable partially has a significant effect on employee performance. The social compensation variable partially has no significant effect on employee performance. Simultaneously the variables of protean career development and social compensation have a significant effect on employee performance 17.5%. And the remaining 82.5% is influenced by other variables.